Scaling up: the BRAC experience - Ahmed, Salehuddin; French, Micaela (BRAC University, 2010)
BRAC, a development NGO based in Bangladesh, has demonstrated an extraordinary aptitude for program expansion, or ‘scaling up’. Only thirty-four years old, the organization is today the largest NGO in the world, with programs serving an estimated 110 million people. This paper identifies the seven key principles of scaling up responsible for BRAC’s success: Listening to the People, Vision, Piloting, Training, Down-to-Earth Management, Evaluation and Adaptation, and Advocacy. The expansion of BRAC’s widely imitated Non-Formal Primary Education furnishes concrete examples of these principles in practice. It is our hope that these lessons, accumulated from BRAC’s long experience, will prove useful to other organizations as they endeavor to expand.